Study of the effects of training and interruptions in training upon cardiorespiratory and anthropometric measures in collegiate wrestlers / by Philip Leonard Colyer. -- - Colyer, Philip Leonard (My University, 1979)
The purpose of this thesis was to examine group responses to training and interruptions in training upon cardiorespiratory and anthropometrica! measures of collegiate wrestlers. The wrestlers (N=ll) were members of the 1978-79 Lakehead University Wrestling Club. A repeated measures design was used during the 18 week training period on resting heart rate, blood pressure, pulmonary function and skinfold thickness which were measured five times at the beginning of each month. A one way analysis of variance was performed in an attempt to find a significant £-ratio. In addition a Tukey Test was performed to determine during which portion of the season significant changes occurred. The results of this study indicated that interruptions in training, due to examinations and Christmas holidays, did not result in a significant change in any of the measured variables. However, significant changes (p < .05) occurred in percent body fat, resting heart rate, forced vital capacity and percentage of predicted vital capacity during the training program.
Keywords: Wrestling Training.; Respiration.; Heart beat.